2004
DOI: 10.1289/ehp.6833
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in Maternal and Newborn Blood Indicate Heightened Fetal Susceptibility to Procarcinogenic DNA Damage

Abstract: Polycyclic aromatic hydrocarbons (PAHs) such as benzo[a]pyrene (BaP) are widespread air contaminants released by transportation vehicles, power generation, and other combustion sources. Experimental evidence indicates that the developing fetus is more susceptible than the adult to carcinogenic effects of PAHs, although laboratory studies in rodents suggest that the dose to fetal tissues is an order of magnitude lower than that to maternal tissues. To assess fetal versus adult susceptibility to PAHs and environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(135 citation statements)
references
References 36 publications
5
127
2
1
Order By: Relevance
“…One of the reasons is that the placenta does not completely protect the fetus from the outside influences (Vähäkangas and Myllynen 2006;Myren et al 2007). Factors that may increase fetal susceptibility include higher rates of cell proliferation, the greater number of target cells at risk, lower immunologic competence, and decreased capacity to activate and detoxify carcinogens as well as to repair DNA (Anderson et al 2000;Perera et al 2004;Whyatt et al 2004). A great number of authors showed that the frequency of damages in genetic material of neonates and children, such as MN and chromosome aberrations, increased with the concentration of environmental agents (Bocskay et al 2005;Milošević-Djordjević et al 2005, 2007bNeri et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons is that the placenta does not completely protect the fetus from the outside influences (Vähäkangas and Myllynen 2006;Myren et al 2007). Factors that may increase fetal susceptibility include higher rates of cell proliferation, the greater number of target cells at risk, lower immunologic competence, and decreased capacity to activate and detoxify carcinogens as well as to repair DNA (Anderson et al 2000;Perera et al 2004;Whyatt et al 2004). A great number of authors showed that the frequency of damages in genetic material of neonates and children, such as MN and chromosome aberrations, increased with the concentration of environmental agents (Bocskay et al 2005;Milošević-Djordjević et al 2005, 2007bNeri et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Socioeconomic and psychosocial factors, including poverty, maternal education, and maternal psychological distress, are important determinants of fetal and child development. [6][7][8][9][10][11][12][13][14][15][16][17] In addition, prenatal maternal stress and maternal psychological distress, reflective of maternal affective or emotional functioning, have also been associated with child behavioral development.…”
mentioning
confidence: 99%
“…Additionally, they illustrate the biologic capacity of nicotine and cotinine to concentrate in the fetus, as suggested in the model by Gentry et al (2003). In five studies, higher biomarker levels were detected in fetal/neonatal samples than in maternal samples (Luck et al, 1985;Nafstad et al, 1995;Jauniaux et al, 1999;Whyatt et al, 2001;Perera et al, 2004).…”
Section: Biomarker Studiesmentioning
confidence: 94%
“…Of the eight studies to be described, five studied populations of both active smokers and non-smoking mothers exposed to ETS (Eliopoulos et al, 1994;Nafstad et al, 1995;Jauniaux et al, 1999;Klein and Koren, 1999;Whyatt et al, 2001;Perera et al, 2004). The remaining studies included only active smokers and non-ETS exposed non-smokers in their analyses (Luck et al, 1985;Donnenfeld et al, 1993;Mercelina-Roumans et al, 1996), but are worthy of discussion because of the added value they bring to understanding exposure to nicotine in the maternal/fetal system.…”
Section: Biomarker Studiesmentioning
confidence: 99%
See 1 more Smart Citation